Scripture and Law in the Dead Sea Scrolls - Jassen, Alex P. (Cambridge University Press, 2014)
3 Jewish Legal Exegesis and the Origins and Development of the CanonI. Introduction; II. The "Old" Model of Canon Formation; III. Toward a New Model of Canon Formation: Literary and Textual Diversity; IV. The Canonical Process and Authority in Second Temple Judaism; Individual Scriptural Books and the Canonical Process; The Pentateuch and the Canonical Process; The "Prophets" and the Canonical Process; V. The Canonical Process and Authority in Rabbinic Judaism; VI. Between Scriptural Formation and Scriptural Interpretation; VII. Conclusions.